2022
DOI: 10.1007/jhep07(2022)010
|View full text |Cite
|
Sign up to set email alerts
|

Higher-derivative holography with a chemical potential

Abstract: We carry out an extensive study of the holographic aspects of any-dimensional higher-derivative Einstein-Maxwell theories in a fully analytic and non-perturbative fashion. We achieve this by introducing the d-dimensional version of Electromagnetic Quasitopological gravities: higher-derivative theories of gravity and electromagnetism that propagate no additional degrees of freedom and that allow one to study charged black hole solutions analytically. These theories contain non-minimal couplings, that in the hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 171 publications
0
4
0
Order By: Relevance
“…The boundary terms associated with a generic higher-derivative bulk action such as (3.15) are not known, although several effective prescriptions have been discussed in the literature before, see e.g. [33,53,54] and references therein. In our simpler effective action (3.7), the only four-derivative invariant for which the associated Gibbons-Hawking term…”
Section: Higher-derivative Boundary Termsmentioning
confidence: 99%
“…The boundary terms associated with a generic higher-derivative bulk action such as (3.15) are not known, although several effective prescriptions have been discussed in the literature before, see e.g. [33,53,54] and references therein. In our simpler effective action (3.7), the only four-derivative invariant for which the associated Gibbons-Hawking term…”
Section: Higher-derivative Boundary Termsmentioning
confidence: 99%
“…First, one could investigate the addition of (nonminimally coupled) matter to Cosmological Gravities, such as a scalar field or a U(1) gauge field. Regarding this last point, it is known that the definition of GQTGs may be canonically extended to allow for non-minimal couplings to a U(1) vector [41,[118][119][120][121], so it makes sense to explore whether a similar situation may occur for Cosmological Gravities, Also, the inclusion of this type of matter has mainly been considered in the context of minimally coupled nonlinear electrodynamics [122][123][124], so this aspect deserves careful scrutiny. Second, a natural question would be the addition of terms with covariant derivatives of the curvature, expected to appear from an effective field theory perspective.…”
Section: Discussionmentioning
confidence: 99%
“…It can be shown that quasi-topological gravity satisfies this condition and thus is a subclass of GQTG. Features of GQTG have been studied comprehensively at present [18][19][20][21][22][23][24][25][26][27]. In particular, (1.2) implies [26] the equation of f (r) is at most second order, the existence of Schwarzschild-like solutions, and most importantly, the decoupling of the extra massive modes.…”
Section: Jhep03(2023)055mentioning
confidence: 99%